Awareness of hypertension-related complications and its determinants among adult hypertensive patients in Ethiopia - Chekol, Habtam Reda; Demissie, Negesu Gizaw; Mekonnen, Chilot Kassa (Frontiers in Cardiovascular Medicine, 2025)
BackgroundHypertension is a critical medical condition that substantially raises the risk of developing heart, brain, kidney, and other organ-related diseases. Despite its significance, limited information is available regarding patients' awareness of hypertension complications and associated factors in the study area. Consequently, this study sought to evaluate the awareness levels of hypertensive patients concerning the risk factors and complications of hypertension.ObjectiveThis study aimed to assess the awareness of hypertension-related complications and the factors influencing it among adult hypertensive patients.MethodsA cross-sectional institutional study was conducted among hypertensive patients. Bivariable and multivariable logistic regression analyses were employed, using odds ratios with 95% confidence intervals and p-values ≤ 0.05 to determine statistically significant associations.ResultsThe study included 422 participants, achieving a 100% response rate. Among the participants, only 42.4% (95% CI: 37.7–47.2) were knowledgeable about hypertension risk factors, complications, and prevention measures. The key predictors of awareness were being an urban resident [AOR = 7.20, 95% CI (3.77–13.76)], attaining a college or higher education level [AOR = 2.28, 95% CI (1.14–6.58)], working as a government employee [AOR = 2.97, 95% CI (1.66–7.05)], using social media [AOR = 6.01, 95% CI (3.37–10.71)], receiving advice from health professionals [AOR = 4.17, 95% CI (2.06–5.88)], attending all follow-up appointments [AOR = 1.88, 95% CI (1.04–2.47)], and having been diagnosed for ten or more years [AOR = 2.33, 95% CI (1.15–4.72)].ConclusionThe study highlighted a significant gap in awareness about hypertension risk factors and complications, with only two-fifths of participants demonstrating adequate knowledge. These findings underscore the need for targeted public health interventions, particularly focusing on rural communities, to bridge the awareness gap.